(untitled) (Journal of Technology and Operations Management, 2025)
Human error is the primary cause of most accidents, leading to various issues and shipping delays. Previous research has identified three key causes that culminate in human error in the Malaysian shipping industry: poor communication, fatigue, and lack of experience. However, there is limited discussion on effective strategies to mitigate these errors. Therefore, this study aims to propose optimal solutions to reduce human error. Through this study, quantitative research methods were used to obtain important data involving the main objectives of this study. For the quantitative analysis, data was collected through multiple rounds of questionnaires distributed to 25 experts using the Delphi method and analysed using the Statistical Package for the Social Sciences (SPSS). The study stresses the critical factors influencing human error in the industry, with findings identifying fatigue as the primary contributor to accidents. Addressing this issue would help the shipping industry to reduce human errors and accidents, thereby ensuring smoother operations.